Synchronous and Asynchronous E-Language Learning: A Case Study of Virtual University of Pakistan - Ayesha Perveen (Open Praxis, 2016)
This case study evaluated the impact of synchronous and asynchronous E-Language Learning activities (ELL-tivities) in an E-Language Learning Environment (ELLE) at Virtual University of Pakistan. The purpose of the study was to assess e-language learning analytics based on the constructivist approach of collaborative construction of knowledge. The courses selected for random sampling were English Comprehension (Eng101), Business & Technical English (Eng201) and Business Communication (Eng301). Three methods were employed to collect the data: observation of the communication and performance on given channels, students’ opinions on Graded Discussion Board (GDB), and a survey questionnaire. Out of a total population of 9919, 1025 responses were received for the survey questionnaire. The findings revealed that asynchronous e-language learning was quite beneficial for second language (L2) learners, but with some limitations which could be scaffolded by synchronous sessions. Based on the findings, the researcher suggested a blend of both synchronous and asynchronous paradigms to create an ideal environment for e-language learning in Pakistan.